1991
DOI: 10.2165/00007256-199112010-00004
|View full text |Cite
|
Sign up to set email alerts
|

Overtraining in Athletes

Abstract: Overtraining appears to be caused by too much high intensity training and/or too little regeneration (recovery) time often combined with other training and nontraining stressors. There are a multitude of symptoms of overtraining, the expression of which vary depending upon the athlete's physical and physiological makeup, type of exercise undertaken and other factors. The aetiology of overtraining may therefore be different in different people suggesting the need to be aware of a wide variety of parameters as m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
240
0
28

Year Published

1998
1998
2011
2011

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 384 publications
(275 citation statements)
references
References 172 publications
7
240
0
28
Order By: Relevance
“…Overtraining, resulting from heavy endurance training without adequate recovery, is also supposed to induce changes in autonomic function (Israel, 1976;Lehmann et al, 1993), Overtraining is a general term that indicates that an individual has been stressed by training and extraneous sttessors to the extent that he/she cannot perform at an optimum level after an appropriate regeneration period. (Fry et al, 1991). Over-reaching is short-term overtraining in which the restoration of performance capacity may take from several days to a few weeks.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Overtraining, resulting from heavy endurance training without adequate recovery, is also supposed to induce changes in autonomic function (Israel, 1976;Lehmann et al, 1993), Overtraining is a general term that indicates that an individual has been stressed by training and extraneous sttessors to the extent that he/she cannot perform at an optimum level after an appropriate regeneration period. (Fry et al, 1991). Over-reaching is short-term overtraining in which the restoration of performance capacity may take from several days to a few weeks.…”
Section: Introductionmentioning
confidence: 99%
“…The criteria for overtraining were (1) decreased maximal oxygen uptake by at least 2 rnl kg-1 min-I, (2) .decreased treadmill performance, (3) unwillingness to train and a feeling of inability to continue training in combination with certain overtraining signs and symptoms, e.g. mood disturbances (decreased positive feelings: energetic, helpful, calm, vigorous, relaxed, confident; and increased negative feelings: irritable, depressed, moody, fatigued, anxious, confused, excited, desperate, unable to concentrate), sleeping problems, menstrual irregularities, bad appetite, trembling hands, sweating or other psychosomatic symptoms, and (4) no illness, injury or other factors explaining the performance decrement (Kuipers & Keizer, 1988;Fry et al, 1991;Hooper & McKinnon, 1995). Five ETG athletes \vere diagnosed as being overtrained and they formed a subgroup of overtrained athletes (OAsubgroup).…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies have reported loss of appetite, due to the arduous training schedule (Mackinnon, 2000;Meeusen et al, 2006), our results showed no differences in food intake between groups (data not shown). Thus, the weight loss observed in the Tr group could also be related to the reduction in plantaris muscle fiber CSA's, although other factors such as loss of motivation, apathy, irritability, and depression could be related to the weight loss (Fry et al, 1991;Mackinnon, 2000).…”
Section: Skeletal Muscle Changes During Resistance Trainingmentioning
confidence: 96%
“…However, when recovery time, volume, and intensity are inadequate, they can cause a series of hormonal and physiological changes in the organism Fry et al, 2005), such as alterations in muscle fibers, a decrease in strength and an increase in protein catabolism, leading to a state called overtraining (Fry et al, 1991;Lehmann et al, 1999). Petibois et al (2003) observed that overtrained individuals presented higher amino acids and lower protein blood accumulation in response to exercise than well-trained individuals, suggesting that proteins were catabolized for amino acid supply during exercise.…”
Section: Skeletal Muscle Changes During Resistance Trainingmentioning
confidence: 99%
See 1 more Smart Citation